Ekonomi Solidaritas sebagai Praktik Resiliensi: Pembacaan Kisah Para Rasul 2:44-47 dalam Membangun Ketahanan Umat di tengah Krisis - Napitupulu, Musa Pardamean (Sekolah Tinggi Teologi Torsina Surakarta, 2023)
The multidimensional crisis from the post-COVID-19 pandemic to contemporary global economic uncertainty leaves Indonesian Christians in a vulnerable position, calling for a constructive theological-practical response. This research reconstructs the meaning of